Justification by the US and India for their border controls against illegal immigration - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
The US and India have strengthened their borders against illegal immigration. However, the two states have striking differences with respect to their border control methods. The US strengthened its Mexican border through fences and militarization. In sharp contrast, even though India fenced some parts of its border, it has relied on shooting practices which have resulted in the deaths of thousands of Bangladeshi immigrants. Drawing upon Narrative Policy Analysis (NPA), this paper identifies patterns in justification strategies regarding border control against illegal immigration in the US and in India. The findings indicate that in the US, border control was justified by the restoration of law at the border. To the contrary, in India, border control was associated with arbitrariness. The majority of Indian policymakers encourage arbitrary border practices by adopting the view that 'any method' is legitimate to curb illegal immigration from Bangladesh.
Keywords: Illegal Immigration; Border Control; Justification Strategies; US; India; COMMISSION; Government & Law